2016
DOI: 10.1089/jamp.2015.1220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flow Rate on In Vitro Aerodynamic Performance of NEXThaler® in Comparison with Diskus® and Turbohaler® Dry Powder Inhalers

Abstract: Background: European and United States Pharmacopoeia compendial procedures for assessing the in vitro emitted dose and aerodynamic size distribution of a dry powder inhaler require that 4.0 L of air at a pressure drop of 4 kPa be drawn through the inhaler. However, the product performance should be investigated using conditions more representative of what is achievable by the patient population. This work compares the delivered dose and the drug deposition profile at different flow rates (30, 40, 60, and 90 L/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 35 publications
2
60
0
Order By: Relevance
“…The NEXThaler device also delivers a so-called 'extrafine beclomethasone and formoterol aerosol' with particles micronized to a mass median aerodynamic diameter (MMAD) <1.5 μm. Chiesi claims to achieve higher lung deposition with better penetration into the small airways with such particles, compared to inhalation powders with a larger MMAD, due to lower oropharyngeal losses [88,89]. The magnesium stearate in the formulation facilitates effective dispersion of such small drug particles.…”
Section: 'Repair Actions' For Design Weaknesses Of Early Dpi Conceptsmentioning
confidence: 99%
“…The NEXThaler device also delivers a so-called 'extrafine beclomethasone and formoterol aerosol' with particles micronized to a mass median aerodynamic diameter (MMAD) <1.5 μm. Chiesi claims to achieve higher lung deposition with better penetration into the small airways with such particles, compared to inhalation powders with a larger MMAD, due to lower oropharyngeal losses [88,89]. The magnesium stearate in the formulation facilitates effective dispersion of such small drug particles.…”
Section: 'Repair Actions' For Design Weaknesses Of Early Dpi Conceptsmentioning
confidence: 99%
“…De Boer et al, 2015) the NEXThaler ® inhaler is a DPI (dry powder inhaler) device delivering an almost pressure-drop independent dose of BDP and FF. It has also been demonstrated that Foster ® NEXThaler ® emits a high fraction of fine (diameter < 5 μm) and extrafine (diameter < 2 μm) particles (Buttini et al, 2016) with high lung deposition efficiency and a more uniform deposition distribution . The special internal design and structure of the inhaler is considered to contribute to the above characteristics of the drug (Scichilone et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The DD from the Turbuhaler was similar, regardless if shaken or not. devices has been extensively studied [16,17]. For analogues to be approved in the European Union (EU), it is a prerequisite that the particle size distribution is similar to the originator product at three different flow rates: low, medium and high [18].…”
Section: Discussionmentioning
confidence: 99%